2004
DOI: 10.1111/j.1746-1049.2004.tb01016.x
|View full text |Cite
|
Sign up to set email alerts
|

The Potato Marketing System and Its Changes in Bangladesh: From the Perspective of a Village Study in Comilla District

Abstract: This paper analyzes the marketing system of potato in Bangladesh, especially the economic relations among farmers, traders, and cold storage owners and elucidates the structural changes in the rural economy through a village study. Investment in the potato market is capital-intensive and risky, and is often considered to be vertically linked. The present study shows that farmers and cold storage owners do not invest in trading because of lack of time and "skill" to deal with urban traders. Besides, farmers fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Notable thing was no higher educated people in Bangladesh were directly involved in the cultivation of potato. Generally potato cultivating farmers can be grouped in to 4 groups-landless (0 acres), small farm size (0.01-0.49 acres), medium farm size (0.50-1.49 acres) and large farm size (≥1.50 acres) (Moazzem and Fujita, 2004). They found that 25% farmers were landless but they cultivate other land that's why they known as borgachasi.…”
Section: Socio-economic Status Of Potato Cultivation Farmersmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable thing was no higher educated people in Bangladesh were directly involved in the cultivation of potato. Generally potato cultivating farmers can be grouped in to 4 groups-landless (0 acres), small farm size (0.01-0.49 acres), medium farm size (0.50-1.49 acres) and large farm size (≥1.50 acres) (Moazzem and Fujita, 2004). They found that 25% farmers were landless but they cultivate other land that's why they known as borgachasi.…”
Section: Socio-economic Status Of Potato Cultivation Farmersmentioning
confidence: 99%
“…In Bangladesh more than 100 vegetables are produced (Rubayet and Jony, 2016). Among a huge variety of vegetables, potato stands first by choice of farmers after introducing some preservation facilities like cold storage and so on (Moazzem and Fujita, 2004). Whole year round demand of potato by consumers and the high perishable rate of other vegetables due to lack of preservation facilities are also responsible for the higher production within last few years though the cultivation of potato was started at late 19 th century in Bangladesh (Baset et al, 2009) in contrast to 17 th century in Indian sub-continent (Pandey et al, 2000) and commercial production of crops was started from 1920 (Hossain et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there are more than hundred palatable foods made from potatoes (Das [6]). Adequate supply of potato stabilizes the vegetable market all around the year (Moazzem and Fujita [7]). Potato are also used in processing industry such as production of starch, alcohol, glucose, dextrin and citric acid in textile and paper industries, inks, dyes, soap and leather processing (Sarker [8]).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of their emergence is not well understood and has led to charges of market power and price manipulation (e.g. Basu, 2010;Moazzem and Fujita, 2004).…”
Section: Introductionmentioning
confidence: 99%